Determining the Levels of Cortisol, Testosterone, Lactic Acid and Anaerobic Performance in Athletes Using Various Forms of Coffee - Gur, Melda; Cinar, Vedat; Akbulut, Taner; Bozbay, Kenan; Yucedal, Polat; Aslan, Mehdi; Migliaccio, Gian Mario (Mdpi, 2024)
Background: Coffee is considered one of the most preferred and consumed beverage types in the world, and caffeine is known to increase physical performance due to its ergogenic properties. The aim of this study is to examine the effects of coffee consumption in different forms on cortisol, testosterone, lactic acid and anaerobic performance levels. Methods: A total of 15 licensed male football players participated in the research voluntarily. The research was implemented in a single-blind, counterbalanced, randomized and crossover study design. Participants were given caffeinated coffee (CK), decaffeinated coffee (placebo) (DK), powdered caffeine (in a gelatin capsule) (PC) and powdered placebo (maltodextrin in a capsule) (PM) on different days, and the Wingate test protocol was performed after the warm-up protocol. Blood samples were collected post-test. Cortisol, testosterone and lactic acid levels in the serum samples taken were determined by the ELISA method. Results: As a result, it was revealed that caffeinated coffee given to participants who exercise increased anaerobic power. However, it was observed that lactic acid levels were higher in placebo and decaffeinated coffee. The highest level of cortisol was found in caffeinated coffee and powdered caffeine compared to the placebo. Testosterone values were observed to be highest in caffeinated coffee and decaffeinated coffee compared to a placebo. Conclusions: The study suggests that the type of caffeine is a factor that affects absorption rate, which impacts performance and hormone levels.
Keywords: biochemical markers; coffee; caffeine; exercise physiology; physical performance; perform aid; hormone; metabolism; wingate test